Informationsressourcen - Gantert, Klaus; Lauber-Reymann, Margrit (De Gruyter, 2023)
This reliable volume provides information specialists with an up-to-date introduction to using information resources. Alongside the theoretical principles, it selects about 400 general and specialist information resources and describes their content, functions, and significance. It thus conveys basic knowledge about information resources that can be used directly in practice.